Assessing climate risks to Net Zero power system in Great Britain - Jaise Kuriakose; Eduardo A. Martínez Ceseña; Ruth Wood (Carbon Management, 2025)
The electrification of heating and surface transport, alongside increased electricity generation from wind and solar, is central to achieving the UK’s Net Zero climate change target. Simultaneously, the UK’s third Climate Change Risk Assessment highlights vulnerabilities in energy infrastructure due to changing climate patterns, including rainfall variability, windstorms, and heatwaves. Against this backdrop, this article evaluates selected 2050 Net Zero energy scenarios and assesses their impact on the vulnerability of Great Britain’s power transmission and distribution networks to climate change. It reviews seasonal climate risks to Net Zero supply and demand technologies and introduces a framework for climate impact analysis, focusing on windstorms. Under a high-emission scenario, increased cooling demand combined with reduced wind energy supply during summers presents a risk, particularly during heat waves, necessitating careful planning of network capacity for system operation. Winter windstorms, which may extend into autumn and spring, pose additional threats to infrastructure at a time of high electricity demand due to heat pumps, potentially leading to power outages. A windstorm impact model based on historical data suggests that while planned network investments may increase capacity, they do not fully prevent outages caused by extreme weather. Demand flexibility emerges as a critical low-regret solution, capable of reducing outages during extreme events. However, significant policy changes are needed to promote widespread flexibility adoption in the UK, addressing both regulatory and social barriers. A diverse portfolio of demand response mechanisms is recommended to enhance system resilience during extreme weather.